Pengaruh Citra Merek, Harga dan Kualitas Layanan Terhadap Minat Membeli Jasa Laundry Shoesbox - Ivan, Julyan Nur; W, Diana Titik; Wahyuni, Etty Sri (Universitas Batam, 2024)
The purpose of this study was to determine and analyze the effect of Brand Image, Price, and Service Quality on Interest in Buying Shoesbox Laundry. The method used in this research is quantitative methods. The population in this research is Shoesbox customers with an average monthly rate of 156 people. The sample for this research was 130 respondents. The data collection technique used in this research was a questionnaire which was tested for validity and reliability. The data analysis technique of this research uses Multiple Linear Regression, Classical Assumption Test, Hypothesis Test (t test and F test), and Coefficient of Determination. Data processing in this study used the SPSS Software program version 25. The results of this study indicate that brand image has a significant positive effect on Purchase Intention for Shoebox Laundry services with a probability value of 0.000 < 0.05. Service Quality has no significant negative effect on Buying Interest for Shoesbox Laundry services with a probability value of 0.173 > 0.05. Brand Image, Price, and Service Quality simultaneously have a significant effect on Purchase Intentions for Shoebox Laundry services with a probability value of 0.000 < 0.05. The Coefficient of Determination value of 83.2% shows the contribution of Brand Image, Price, and Service Quality to Interest in Buying Shoesbox Laundry services and the remaining 16.8% is explained by various other variables.